The Effects of Alcohol Excise Tax Increases by Drinking Level and by Income Level - Henry Saffer; Markus Gehrsitz; Michael Grossman (Institute of Labor Economics (IZA), 2022)
The alcohol industry argues that alcohol excise taxes do not reduce heavy drinking because of substitutions to lower-cost products and that these taxes disproportionately burden low-income drinkers. Alternatively, some economists have argued that increases in alcohol excise taxes reduce heavy alcohol consumption. Using data from the Nielsen Homescan we investigate the effects of a large excise tax increase that raised alcohol prices. The results show that heavy drinkers reduce purchases, and this reduction is no different than the reductions by other drinkers. The results also show that only low-income drinkers pay more for ethanol after the tax increase.
Keywords: I18; H20; 330; alcohol; excise tax; heavy drinking; low income